(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
Background: Defects of the lower eyelid can result from various etiologies, and reconstruction of the defects is a challenge in daily practice, imposed by its functional and cosmetic relevance. Many different flaps and grafts have been described for reconstruction, and there is a little evidence which method is best. Objective: The aim of this study is to evaluate reconstruction of lower eyelid defects with various skin flaps and grafts and determining the cosmetic and functional results of each method, and the resulting complications. Patients and Methods: A Prospective Study conducted for the period one years (2019-2020) at Tishreen University Hospital in Lattakia-Syria. included 30 patients with lower eyelid defect who underwent to reconstruction by using various flaps. Results: Median age was 54 years, and female represented 63.3% of the patients. Tumors represented the frequent etiology of defects (73.3%), especially basal cell carcinoma (56.7%), followed by trauma (20%). The size of defect was 25-50% in 53.4%. Primary closure was applied in small size defect, and various flaps in medium-large defects, with complete success in 88-100%. Epiphora was developed in 6 cases (20%) and ectropion in 3 cases (10%), cosmetic results were better with Tenzel flap with lower rate of complications. Conclusion: Using of Tenzel flap may be more likely to result in best cosmetic and functional outcomes, with low rate of complications. Keywords: Lower eyelid defects, flaps, outcome